Fouling-Resistant Zwitterionic Copolymer Membranes with Advanced Selectivity - Lounder, Samuel. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Ayse Asatekin.; Committee: Matthew Panzer, Peggy Cebe, and Douglas Gin.; Keywords: Chemical engineering, and Polymer chemistry.